Rituximab for minimal-change nephrotic syndrome in adulthood: predictive factors for response, long-term outcomes and tolerance - Guitard, Joëlle; Hebral, Anne-Laure; Fakhouri, Fadi; Joly, Dominique; Daugas, Eric; Rivalan, Joseph; Guigonis, Vincent; Ducret, Françis; Presne, Claire; Pirson, Yves; Hourmant, Maryvonne; Glachant, Jean-Claude; et al. (Nephrology, dialysis, transplantation, 2014)
Minimal-change nephrotic syndrome (MCNS) is a common cause of steroid sensitive nephrotic syndrome (NS) with frequent relapse. Although steroids and calcineurin inhibitors (CNIs) are the cornerstone treatments, the use of rituximab (RTX), a monoclonal antibody targeting B cells, is an efficient and safe alternative in childhood. Because data from adults remain sparse, we conducted a large retrospective and multicentric study that included 41 adults with MCNS and receiving RTX. Complete (NS remission and withdrawal of all immunosuppressants) and partial (NS remission and withdrawal of at least one immunosuppressants) clinical responses were obtained for 25 and 7 patients, respectively (overall response 78%), including 3 patients that only received RTX and had a complete clinical response. After a follow-up time of 39 months (6-71), relapses occurred in 18 responder patients [56%, median time 18 months (3-36)]. Seventeen of these received a second course of RTX and then had a complete (n = 13) or partial (n = 4) clinical response. From multivariate analysis, on-going mycophenolate mofetil (MMF) therapy at the time of RTX was the only predictive factor for RTX failure [HR = 0.07 95% CI (0.01-0.04), P = 0.003]. Interestingly, nine patients were still in remission at 14 months (3-36) after B-cell recovery. No significant early or late adverse event occurred after RTX therapy. RTX is safe and effective in adult patients with MCNS and could be an alternative to steroids or CNIs in patients with a long history of relapsing MCNS.